Adsorption of Fluoride from Water Using Aluminum-Coated Silica Adsorbents: Comparison of Silica Sand and Microcrystalline Silica - Kiana Modaresahmadi; Amid P. Khodadoust; James Wescott (Separations, 2024)
Two aluminum-coated silica adsorbents were evaluated using silica sand and microcrystalline silica as aluminum-oxide-based adsorbents with different crystalline silica base materials. The aluminum coating contained mainly amorphous aluminum oxides for both aluminum-coated silica adsorbents. The adsorption of fluoride onto both adsorbents was favorable according to the Langmuir and Freundlich adsorption equations, while the physical adsorption of fluoride occurred for both adsorbents according to the Dubinin–Raduskevish (D-R) equation. The adsorption of fluoride was stronger for aluminum-coated silica sand based on adsorption parameters from the Langmuir, Freundlich, and D-R adsorption equations, with the stronger binding of fluoride likely due to the observed greater specific adsorption. The adsorption capacity determined using the Langmuir equation was about 7 times greater for aluminum-coated microcrystalline silica primarily due to the 1.22-orders-of-magnitude-larger surface area of aluminum-coated microcrystalline silica, whereas the surface-normalized adsorption capacity was 2.4 times greater for aluminum-coated silica sand, possibly due to more aluminum being present on the surface of silica sand. Fluoride adsorption occurred over a broad pH range from 3 to 10 for both adsorbents, with nearly the same pHPZC of 9.6, while aluminum-coated microcrystalline silica displayed a higher selectivity for fluoride adsorption from different natural water sources.